2008
DOI: 10.1088/0953-2048/21/6/062001
|View full text |Cite
|
Sign up to set email alerts
|

Further increase of the critical current density of MgB2tapes with nanocarbon-doped mechanically alloyed precursor

Abstract: The combination of nanocarbon-doped nanosized MgB 2 precursor powder with an inert metallic sheath of appropriate hardness gives the possibility to obtain tapes with significantly improved critical current densities at high magnetic fields. In parallel field, J c -values of 10 4 A cm −2 at 16.4 T (4.2 K) and 5.6 T (20 K) could be measured.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
59
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
3
3

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(60 citation statements)
references
References 12 publications
1
59
0
Order By: Relevance
“…The transport critical current (I c ) of the MgB 2 wires was measured with the four-probe resistive method at 4.2 K up to 150 A in a perpendicular magnetic field at the International Laboratory of High Magnetic Fields and Low Temperatures in Wrocław [17,18]. Transport critical current measurements at 20 K were conducted at the Institute for Solid State and Materials Research Dresden [19]. The I c was determined on the basis of 1 μV/cm criterion.…”
Section: Preparation Of Samplesmentioning
confidence: 99%
“…The transport critical current (I c ) of the MgB 2 wires was measured with the four-probe resistive method at 4.2 K up to 150 A in a perpendicular magnetic field at the International Laboratory of High Magnetic Fields and Low Temperatures in Wrocław [17,18]. Transport critical current measurements at 20 K were conducted at the Institute for Solid State and Materials Research Dresden [19]. The I c was determined on the basis of 1 μV/cm criterion.…”
Section: Preparation Of Samplesmentioning
confidence: 99%
“…I hope that further research and development with the aim of meeting the above requirements in addition to J c improvement will lead to the practical applications of superconducting wires in future. 17) a Mg-diffusion-processed MgB 2 wire, 18) a PLD-processed MgB 2 thin film, 19) a Nb-Ti wire, and a Nb 3 Sn wire are also shown. …”
Section: Discussionmentioning
confidence: 99%
“…Haßler et al [33] have reported the highest J c (10 4 A/cm 2 at 16.4 T and 4.2 K) at high magnetic fields by high-energy ball milling technique with nanocarbon alloying. This excellent performance can be attributed to the nanocrystalline grain size with a high amount of grain boundaries, and the effectivity of carbon substitution by mechanical alloying [34,35].…”
Section: Carbon Dopingmentioning
confidence: 99%